Quantitative Evaluation of Cloud ERP Dialectics on Professional Collaboration and Organizational Performance - Adi Nugroho, Cahyo; Bratakusuma, Sumantri (Advances in Accounting Innovation, 2025)
Objective: Assess the impact of business and technology logic orientations, collaboration mechanisms, and innovation culture digital readiness on cloud ERP implementation and organizational performance.Methods: A quantitative PLS-SEM analysis was conducted on 216 managers from mid to large-sized companies.Results: Business logic orientation and collaborative mechanisms were found to positively contribute to cloud ERP success (CEIS), while technical logic orientation was found to have a negative impact. CEIS directly impacts firm performance positively. Furthermore, IC and DR significantly moderates the relationship between collaboration and CEIS, suggesting the importance of contextual readiness. R² and Q² values of 0.50 and 0.35, respectively, are considered good for explanatory and predictive qualities. The HTMT values provide strong evidence of convergent validity.Novelty: This study is distinctive because it integrates the logic of leadership, the practices of collaboration, and the culture of digital readiness from a dialectical perspective to explain the outcomes of ERP. It also recognizes and empirically substantiates the significant role of innovation culture/digital readiness, which has been scantily studied in the ERP context, in moderating change dynamics in digital transformation projects.Research Implications: To enhance ERP outcomes, practitioners should prioritize adaptive leadership, promote a collaborative, cross-functional culture, and train for digital readiness. Dependence on inflexible technical logic can be counterproductive in volatile settings. This article provides a diagnosis and a roadmap for achieving organizational agility and resilience in Cloud-ERP transformation.